Issues on VMAT QA Program with EBT3 Radiochromic Films: An improvement proposal - Dal Col, Alisson Henrique; Nagao, Alexandre; dos Santos, William Alves Pinto; Pena, Geovani Pires; Pelosi, Edilson Lopes; Neves-Junior, Wellington Furtado Pimenta; Haddad, Cecilia Maria Kalil (Revista Brasileira de Física Médica, 2018)
EBT3 radiochromic film is renowned in medical physics field due its dose verification for Quality Assurance (QA) program in intensity-modulated radiotherapy (IMRT). However, it is known that QA programs, which include these films, are expensive and relatively time-consuming. Furthermore, it was noted that dosimetry with EBT3 film has been suffering with lack of accuracy. In that way, it was evaluated its possible dosimetric inaccuracy, the time expenditure in the whole QA process, as well as the cost-benefit of such a program and it is suggested efforts to improve this process based on our institution expertise. A retrospective study was performed on VMAT plans, rating how many cases got success by absolute dosimetric Gamma analysis. Furthermore, in order to verify the film intra-lot aging, the calibration curves were compared to the lot fabrication date. On the other hand, with single- and multi-channel dosimetric analyses, further trials were performed over the post-irradiation saturation curves up to 35 h after irradiation. The retrospective Gamma analyses exhibited that about 23% of the total VMAT cases did not passed by absolute Gamma evaluation. It was seen that the fabrication date influences the dose response, which prerequisites a calibration curve for each film box. For the multichannel analyses, as excepted, the red channel sensitivity was the highest for doses up to 5 Gy. Moreover, it was reinforced that the dose response is a direct function of dose level for both types of analyses. In that way, it was chosen a post-irradiation time interval of 12h-16h, with dose response variation criteria less than 2%. Finally, it was verified, based on our routine, that there were about 23h/month expended in a film QA program and directly costs bordering US20,000.00/year.